2013
DOI: 10.1007/s00247-013-2824-9
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for anti-scatter grid use in pediatric digital radiography

Abstract: Removing the anti-scatter grid for small patients reduces patient dose without a substantial increase in scatter-to-primary ratio when the FOV is restricted appropriately. Radiologic technologists should base anti-scatter grid use on patient thickness and FOV rather than age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…A statistical comparison of the distributions of patient weights in each sub-group was thus performed to check for this potential source of bias. The results of other studies also report a reduction in dose after removal of the grid, while the level of reduction varies considerably from study to study (7). The results of our study show that removing the grid did not reduce the image quality.…”
Section: Discussionsupporting
confidence: 65%
“…A statistical comparison of the distributions of patient weights in each sub-group was thus performed to check for this potential source of bias. The results of other studies also report a reduction in dose after removal of the grid, while the level of reduction varies considerably from study to study (7). The results of our study show that removing the grid did not reduce the image quality.…”
Section: Discussionsupporting
confidence: 65%
“…Older children in general have a larger body mass (weight and thickness), causing more scattered radiation [ 21 ] that can be corrected by the software. Therefore, anti-scatter grids should only be used for older children [ 8 ] or according to newer insights for chest sagittal diameter greater than 12–15 cm [ 22 ]. Further, use of SimGrid was more effective for higher exposure conditions, which also relates to greater mass and body thickness of older patients causing more scattered radiation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, there are guidelines suggesting the use of anti-scatter grids for children older than 8 years [ 8 ]. There are also publications demonstrating that the sagittal diameter is a better factor [ 1 ] than patient weight and might be included in future guidelines [ 22 ]. As chest diameter of the patients was not available in our system, we grouped patients based on their weight.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric cardiac catheterization, Gould et al [27] reported a 30% decrease in DNA double-strand breakages with grid removal. Fritz et al [28] also found that the benefit of the antiscatter grid in pediatric abdominal radiographs decreases in smaller patients and proposed not using it in certain situations. They discussed that some high patient contrast situations, such as evaluating for air-fluid levels, do not require as high of contrast to adequately evaluate.…”
Section: Discussionmentioning
confidence: 99%